2004
DOI: 10.1111/j.1600-6143.2004.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Artery Chemoembolization for Hepatocellular Carcinoma in Patients Listed for Liver Transplantation

Abstract: We retrospectively analyzed all listed patients having hepatic artery chemoembolization (HACE) for hepatocellular carcinoma (HCC) stage T2 or less. Outcomes were transplantation, waiting list removal, death, and HCC recurrence. Twenty patients (mean age 55.7 years; 15 males) were identified. Twelve (60%) were transplanted, seven (35%) were removed from the list and one (5%) remains listed. Fourteen (70%) are alive. All 12 transplanted patients are alive (mean 2.94 years); one of seven removed from the list is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
1
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 18 publications
1
62
1
4
Order By: Relevance
“…On the basis of the previously discussed definitions, these points can be addressed with a review of the literature; the main studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] are summarized in Table 1. Ideally, studies should include a large number of cases, clearly separate treated and untreated patients, and specify details (treatment, surveillance, dropout, recurrence, and causes of death).…”
Section: Aims Of Management Strategiesmentioning
confidence: 99%
“…On the basis of the previously discussed definitions, these points can be addressed with a review of the literature; the main studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] are summarized in Table 1. Ideally, studies should include a large number of cases, clearly separate treated and untreated patients, and specify details (treatment, surveillance, dropout, recurrence, and causes of death).…”
Section: Aims Of Management Strategiesmentioning
confidence: 99%
“…Various reports had suggested some of patients could be bridged as well as downstaged, which resulted in favorable long-term outcome (43)(44)(45)(46). Unfortunately, not all patients responded to TACE.…”
Section: Transarterial Chemoembolization (Tace)mentioning
confidence: 99%
“…Authors concluded that there was no sufficient evidence to provide a response due to the absence of prospective comparative studies [14]. Hayashi et al reported a discouraging 35% of drop out rate in patients with stage 1 or 2 HCC and with a mean waiting time of 340 days treated with TACE [15]. However, an analysis of the most recent series including patients treated with TACE or transarterial chemoinfusion before LT, showed that the drop out rate due to tumor progression is low, ranging between 2.9% and 13% with a mean waiting time in the transplant list exceeding 6 months ( Table 1) [16][17][18][19].…”
Section: Transarterial Chemoembolizationmentioning
confidence: 99%